Pemanfaatan WebGIS Untuk Pemetaan Sebaran Objek Wisata Di Kecamatan Kemiling Kota Bandar Lampung - Oktaviani, Dwi; Nugraheni, Irma Lusi; Istiawati, Novia Fitri; Miswar, Dedy (Universitas Veteran Bangun Nusantara, 2024)
This study aims to map the distribution of Rabbit Garden Tourism Objects, Durian Farm and Stable Valley, Tahura Wan Abdul Rachman, Gita Persada Butterfly Park, Rainbow Slide, Camp 91, Kampoeng Vietnam, Paraduta Hill, Curved Sky II, Kemiling Hill Permai Housing Complex Valley Tourism Park, Star Hill, Betung Garden, Pelangi Valley, Vietnam Cliff, and Nature Gate in the Kemiling District of Bandar Lampung City by using WebGIS as a web. This study uses a quantitative descriptive method. The data collection technique is observation, interview and documentation. The data analysis technique is descriptive analysis. The results of this study are webguard-based tourist maps, contain information: accessibility, facilities, infrastructure, appeal, security and comfort and users by using quantumGIS, plugins QGIS12Web, leaflet and github as a webhositing. Validity test scores for SIG (System Information Geography) (3,36), pragmatic (3,54), and user (3,72). This means that webGIS gate value with the good category of each expert, which also revision. However, the revision has been repaired by the researcher. The results of the usability test results are 80,46%. This means that webGIS is included in the proper category and has fulfilled usability testing criteria and can be used by users effectively, efficiently and gives the user to use it.